Secreted cell signaling molecules in axon guidance. - Yoshikawa, S.; Thomas, J.B. (Current Opinion in Neurobiology, 2004)
The growth cones of developing neurons respond to specific guidance cues in their extracellular environment. Recent studies have shown that secreted signaling molecules from protein families that are best known for their roles as morphogens in specifying cell fate can function as axon guidance molecules. These signaling molecules seem to act directly on the growth cone and thus are likely to activate non-canonical signaling pathways that are coupled to the cytoskeleton.